The integrated model of consciousness - Smith, Graeme E (PeerJ PrePrints, 2014)
Consciousness is simple by definition, and complex by extension. For the first time we may have a look into some of the complexities of Human Consciousness, and how they may have accreted to core consciousness over millenia. From a Core Consciousness that can be traced to the Optical Tectum in early pre-amphibious ancestors, or even earlier in the evolutionary record, to an advanced model that includes at least 6 different sub-models, and grew from an early model of consciousness, we will see the accretion of layers of consciousness upon the basic core consciousness despite setbacks and variations in the evolution of the brain. Similar to some theories that make the mistake of Scala Naturae this theory shows a scale of elaboration that is not meant to reflect the pattern of evolution, merely a list of elaborations that has become standard within the human brain. It is not meant to be exhaustive, merely indicative of the complexity of consciousness as experienced by human beings. That the stages in development of the human brain make a track through time, is not meant to mean that in fact this track was as straight forward or simple as the model might suggest.
Keywords: Consciousness; defintion of consciousness; Human Consciousness; Optical Tectum; Superior Colliculus; Basal Ganglia; Insula; Precuneus; Integrated Model of Consciousness; Elaborations